A eutectic molecular sieve containing rare earth and a preparation method thereof

The rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieves were prepared by in-situ synthesis, which solved the problems of difficult introduction of rare earth elements and complex post-modification treatment in the existing technology, achieved high catalytic activity and low-carbon olefin yield, and are suitable for catalytic cracking reactions of light hydrocarbons.

CN116924425BActive Publication Date: 2025-10-10CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210342781.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-10-10
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

In the existing technology, it is difficult to effectively introduce rare earth elements when preparing SSZ-13 and SSZ-23 molecular sieves, and the traditional post-modification treatment steps are complicated, resulting in a long synthesis process and high cost, and large product losses.

Method used

The rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieves were prepared by an in-situ synthesis method by mixing a complexing agent, water, a soluble rare earth compound, an alkali source, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, an aluminum source, and a silicon source, and crystallizing them under hydrothermal conditions, thus avoiding the subsequent complex rare earth modification steps.

Benefits of technology

The uniform distribution of rare earth elements in the molecular sieve is achieved, the synthesis process time and cost are shortened, the catalytic activity and the yield of light olefins are improved, and in particular, excellent reaction conversion rate and high yield are exhibited in the catalytic cracking reaction of light hydrocarbons.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116924425B_ABST
    Figure CN116924425B_ABST
Patent Text Reader

Abstract

The application discloses a eutectic molecular sieve containing rare earth, characterized in that the molecular sieve has the characteristic peaks of SSZ-13 molecular sieve and SSZ-23 molecular sieve in an XRD diffraction spectrum, the molar ratio of silicon oxide to aluminum oxide is 5-50, and the rare earth content is 0.5-10%. A preparation method of the eutectic molecular sieve comprises the following steps: uniformly mixing a complexing agent, water and a soluble rare earth compound to obtain a mixture A; adding an alkali source, N, N, N-trimethyl-1-adamantyl ammonium hydroxide, an aluminum source and a silicon source into the mixture A to uniformly mix to obtain a mixture B; and performing a crystallization reaction on the mixture B under a hydrothermal condition and recovering a crystallization product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of molecular sieves and their preparation, and more particularly to a rare earth-containing eutectic molecular sieve and its preparation method. Background Art

[0002] Molecular sieves are a class of commercially important crystalline materials with strong acidity, large surface area, unique pore structure, and stable physicochemical properties. Consequently, they are used as heterogeneous catalysts in many industrial processes.

[0003] SSZ-13 molecular sieve is a molecular sieve with a CHA topology. Its structure consists of aluminum oxide tetrahedra and silicon oxide tetrahedra connected end-to-end through oxygen atoms at their vertices, forming an ellipsoidal cage (0.73×1.2 nm) with an eight-membered ring structure and a three-dimensional intersecting pore structure with a pore size of 0.38×0.38 nm, making it a small-pore molecular sieve. Due to its small pore size, SSZ-13 molecular sieve is currently widely used in gas separation and shape-selective catalysis. The synthesis method of SSZ-13 molecular sieve was first disclosed in US Pat. No. 4,544,538. This synthesis method uses N,N,N-trimethyl-1-adamantyl ammonium hydroxide as a template. The template, silicon source, aluminum source, alkali metal salt, and water are uniformly mixed and hydrothermally crystallized at 100-235°C for more than 3 days to obtain SSZ-13 molecular sieve.

[0004] SSZ-23 molecular sieve is a molecular sieve with an STT topology, containing both seven-membered and nine-membered rings. The seven-membered rings measure 0.35 × 0.24 nm, while the nine-membered rings measure 0.53 × 0.37 nm. Due to its unique pore structure, it exhibits excellent adsorption properties and selectivity, and is currently widely used in gas separation and catalytic reactions. US Patent No. 4,859,442 discloses a method for preparing SSZ-23 molecular sieves using adamantane quaternary ammonium ions as a template. This method involves uniformly mixing the template, a silicon source, an aluminum source, and an alkali metal halide, followed by crystallization in a hydrothermal reactor at 140–200°C for 3–7 days. The product is then filtered, washed, and dried to obtain SSZ-23 molecular sieve.

[0005] Rare earth metal elements are typically introduced into molecular sieves through post-modification. In Y-type molecular sieves, rare earth elements stabilize the aluminum framework. CN103508467A discloses a method for preparing a rare earth Y molecular sieve, which is obtained through a single liquid-phase rare earth ion exchange and a single solid-phase rare earth ion migration. The rare earth Y molecular sieve prepared by this method exhibits good structural and activity stability. Summary of the Invention

[0006] One of the purposes of the present application is to provide a rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieve, the second purpose is to provide a preparation method thereof, and the third purpose is to provide an application of the rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieve.

[0007] To achieve one of the above purposes, the present application provides a rare earth-containing eutectic molecular sieve, characterized in that: in the XRD diffraction spectrum of the molecular sieve, characteristic peaks of SSZ-13 molecular sieve appear at 9.5°, 13.0°, 16.1°, 17.9° and 20.8°, characteristic peaks of SSZ-23 molecular sieve appear at 8.1°, 8.5°, 9.5°, 10.5° and 18.5°, and the molar ratio of silicon oxide to aluminum oxide is 5-50, and the content of the rare earth, calculated as the oxide of the rare earth and based on the dry weight of the eutectic molecular sieve, is 0.5-10%.

[0008] In the eutectic molecular sieve, the molar ratio of silicon oxide to aluminum oxide is preferably 15-35, and the content of the rare earth is 0.5-10%, preferably 1-6%.

[0009] In the eutectic molecular sieve, the rare earth is selected from at least one of lanthanum, cerium and yttrium.

[0010] To achieve the second purpose, the present application further provides a preparation method of the rare earth-containing eutectic molecular sieve, characterized by comprising the following steps: uniformly mixing a complexing agent, water and a soluble rare earth compound to obtain a mixture A; adding an alkali source, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, an aluminum source and a silicon source to the mixture A to uniformly mix to obtain a mixture B; performing a crystallization reaction on the mixture B under hydrothermal conditions and recovering a crystallization product to obtain the rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieve.

[0011] In the preparation method, the complexing agent is preferably selected from at least one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, triethanolamine and triethylamine. The soluble rare earth compound is selected from at least one of lanthanum chloride, yttrium nitrate and cerium nitrate. The alkali source is selected from at least one of sodium hydroxide and potassium hydroxide. The N,N,N-trimethyl-1-adamantyl ammonium hydroxide is preferably an aqueous solution with a mass fraction of 15-30%. The aluminum source is selected from at least one of SB powder, aluminum alcoholate, aluminum oxide, aluminum hydroxide, aluminum sulfate and bayerite. The silicon source is selected from at least one of silica sol, silicon dioxide, white carbon black, silicate and solid silica gel.

[0012] In the preparation method, the molar ratio of the complexing agent to the soluble rare earth compound in the mixture A is preferably 0.1-3:1, and the soluble rare earth compound is calculated as the rare earth oxide. In the mixture B, the molar ratio of water, N,N,N-trimethyl-1-adamantylammonium hydroxide, the aluminum source and the silicon source is preferably 50-1000:0.4-10:1:5-50, the aluminum source is calculated as Al2O3, and the silicon source is calculated as SiO2. The molar ratio of the soluble rare earth compound to the silicon source is preferably 1:10-1000, the soluble rare earth compound is calculated as the rare earth oxide, and the silicon source is calculated as SiO2.

[0013] In the preparation method, the crystallization reaction is preferably carried out under a closed condition at a temperature of 140-200℃ for 18-168h.

[0014] The application provides the rare earth-containing co-crystal molecular sieve obtained by the above preparation method.

[0015] To achieve the third object of the application, the application further provides the application of the rare earth-containing co-crystal molecular sieve. The rare earth-containing co-crystal molecular sieve is applied in catalytic cracking and catalytic cracking as an active component of a catalyst or an additive.

[0016] The application is a method for in-situ synthesis to obtain a rare earth-containing SSZ-13 and SSZ-23 co-crystal molecular sieve product and the application of the co-crystal molecular sieve in light hydrocarbon catalytic cracking reaction. The rare earth-containing co-crystal molecular sieve provided by the application has both characteristic peaks of the SSZ-13 molecular sieve and characteristic peaks of the SSZ-23 molecular sieve. The preparation method of the rare earth-containing SSZ-13 and SSZ-23 co-crystal molecular sieve provided by the application is prepared by using the in-situ synthesis method, which avoids subsequent complex rare earth modification treatment steps, is less than the treatment steps of introducing rare earth elements in the molecular sieve by the commonly used impregnation method and ion exchange method at present, shortens the time and cost of the synthesis process, and avoids the loss of the molecular sieve product in the post-treatment process. The rare earth-containing co-crystal molecular sieve provided by the application is applied in light hydrocarbon catalytic cracking reaction, has high catalytic activity and low carbon olefin yield. BRIEF DESCRIPTION OF DRAWINGS

[0017] Figure 1 The X-ray diffraction spectra of Example 1 sample S-1, Comparative Example 1 sample D-1 and Comparative Example 2 sample D-2. DETAILED DESCRIPTION

[0018] The application will be further described by examples, but the application is not limited in any way by the examples.

[0019] The instruments and reagents used in the examples of the application are all the instruments and reagents commonly used by those skilled in the art, unless otherwise specified.

[0020] In the examples and comparative examples, the elemental chemical composition of the molecular sieves was determined by X-ray fluorescence method using the standard method of GB / T30905-2014.

[0021] In the Examples and Comparative Examples, X-ray diffraction spectra were measured on a Rigaku TTR-3 powder X-ray diffractometer with the following instrument parameters: copper target (tube voltage 40 kV, tube current 250 mA), scintillation counter, step width 0.02°, and scan rate 0.4° / min.

[0022] The effect of molecular sieves on the yield and conversion of light olefins in the catalytic cracking of light hydrocarbons was evaluated using a pure hydrocarbon microreactor. The reaction was carried out in a fixed bed reactor with 1-octene as the feedstock, nitrogen as the carrier gas at a flow rate of 30 mL / min, a reaction temperature of 550°C, a regeneration temperature of 600°C, and a weight space velocity of 40 hr. -1 The molecular sieve was sieved into 20-40 mesh particles after tableting, the filling amount was 2.0 g, the agent-oil ratio was 1.28, and samples were taken for analysis after reacting for 70 seconds and nitrogen purging for 900 seconds, and material balance calculation was performed.

[0023] Example 1

[0024] This example illustrates the rare earth-containing eutectic molecular sieve and its preparation according to the present invention.

[0025] 2.06 g of disodium ethylenediaminetetraacetate and 0.70 g of anhydrous lanthanum chloride were added to 38.21 g of deionized water and stirred for 30 min. 1.57 g of sodium hydroxide, 47.14 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 19.49%) and 0.88 g of SB powder (containing 73.6% Al2O3 mass fraction) were added to the solution in sequence. After stirring for 15 min, 15 g of solid silica gel (containing 77.4% SiO2 mass fraction) was added to the solution. The mixture was stirred and dispersed at room temperature for 3 h, transferred to a hydrothermal autoclave, crystallized at 160 ° C for 60 h, filtered, washed to pH = 7-8, dried at 120 ° C for 12 h, and then calcined at 600 ° C for 6 h to obtain a molecular sieve product containing rare earth lanthanum. After exchange with a soluble ammonium salt at 80 ° C for 2 h, a hydrogen-type molecular sieve was obtained. The product sample was recorded as S-1.

[0026] The XRD spectrum of sample S-1 is shown in Figure 1 As shown in S-1, Figure 1 It can be seen that sample S-1 has characteristic peaks of SSZ-13 molecular sieve at 9.5°, 13.0°, 16.1°, 17.9°, and 20.8°, and characteristic peaks of SSZ-23 molecular sieve at 8.1°, 8.5°, 9.5°, 10.5°, and 18.5°, indicating that the molecular sieve product is a co-crystal molecular sieve of SSZ-13 and SSZ-23.

[0027] The molar ratio of silicon oxide to aluminum oxide is 28, and the rare earth content in the molecular sieve is 2.8% based on the dry weight of the molecular sieve.

[0028] The sample S-1 was subjected to pure hydrocarbon micro-reaction evaluation after being hydrothermally aged at 800℃ under 100% steam for 17h. The micro-reaction evaluation conversion rate, product yield and other data are shown in Table 1.

[0029] Example 2

[0030] This example illustrates the rare earth-containing eutectic molecular sieve of the present application and its preparation.

[0031] To 96.12g of deionized water, 4.80g of ethylenediaminetetraacetic acid and 4.94g of Y(NO3)3·6H2O were added and stirred for 30min, to the solution, 5.22g of sodium hydroxide, 78.57g of N,N,N-trimethyl-1-adamantylammonium hydroxide solution (mass fraction of 19.49%) and 2.21g of SB powder (containing Al2O3 mass fraction of 73.6%) were sequentially added, and after stirring for 15min, 25g of white carbon black (containing SiO2 mass fraction of 73.2%) was added to the solution, and stirred and dispersed at room temperature for 3h, and then transferred to a hydrothermal kettle, and crystallized at 160℃ for 60h, filtered, washed to pH=7-8, dried at 120℃ for 12h, and then calcined at 600℃ for 6h to obtain a rare earth-containing yttrium molecular sieve product, which was then exchanged with a soluble ammonium salt at 80℃ for 2h to obtain a hydrogen type molecular sieve, and the product sample was recorded as S-2.

[0032] The XRD spectrum of the sample S-2 has the same characteristics as Figure 1 S-1 in the present application, indicating that the molecular sieve product is a SSZ-13 and SSZ-23 eutectic molecular sieve.

[0033] The molar ratio of silicon oxide to aluminum oxide is 19, and the rare earth content in the above-mentioned molecular sieve is 5.3% based on the dry weight of the molecular sieve.

[0034] The sample S-2 was subjected to pure hydrocarbon micro-reaction evaluation after being hydrothermally aged at 800℃ under 100% steam for 17h, and the micro-reaction evaluation conversion rate, product yield and other data are shown in Table 1.

[0035] Example 3

[0036] This example illustrates the rare earth-containing eutectic molecular sieve of the present application and its preparation.

[0037] 1.69g of disodium ethylenediaminetetraacetate and 2.39g of CeCl3·7H2O were added to 22.01g of deionized water and stirred for 30min. 2.63g of sodium hydroxide, 51.46g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 25%) and 1.90g gibbsite (containing 65.4% Al2O3 mass fraction) were stirred for 15 minutes, and then 25g white carbon black (containing 73.2% SiO2 mass fraction) was added to the solution. The mixture was stirred and dispersed at room temperature for 3 hours, transferred to a hydrothermal kettle, crystallized at 160°C for 72 hours, filtered, washed to pH = 7-8, dried at 120°C for 12 hours, and then calcined at 600°C for 6 hours to obtain SSZ-13 and SSZ-23 eutectic molecular sieves containing rare earth cerium. After exchange with a soluble ammonium salt at 80°C for 2 hours, an H-type molecular sieve was obtained. The product sample was recorded as S-3.

[0038] The XRD spectrum of sample S-3 is Figure 1 S-1 has the same characteristics, indicating that the molecular sieve products are SSZ-13 and SSZ-23 eutectic molecular sieves.

[0039] The molar ratio of silicon oxide to aluminum oxide is 25, and the rare earth content of the molecular sieve is 3.9% based on the dry weight of the molecular sieve.

[0040] After sample S-3 was hydrothermally aged at 800°C and 100% steam for 17 h, it was subjected to pure hydrocarbon micro-reaction evaluation. The data such as micro-reaction evaluation conversion rate and product yield are listed in Table 1.

[0041] Example 4

[0042] This example illustrates the rare earth-containing eutectic molecular sieve and its preparation according to the present invention.

[0043] 1.23 g of disodium ethylenediaminetetraacetate and 0.52 g of anhydrous lanthanum chloride were added to 40.25 g of deionized water and stirred for 30 min. 3.13 g of sodium hydroxide, 36.75 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 25%) and 2.26g gibbsite (containing 65.4% Al2O3 mass fraction) were stirred for 15 minutes, and then 15g solid silica gel (containing 77.4% SiO2 mass fraction) was added to the solution. The mixture was stirred and dispersed at room temperature for 3 hours, transferred to a hydrothermal autoclave, crystallized at 150°C for 84 hours, filtered, washed to pH = 7-8, dried at 120°C for 12 hours, and then calcined at 600°C for 6 hours to obtain SSZ-13 and SSZ-23 eutectic molecular sieves containing rare earth lanthanum. After exchange with soluble ammonium salts at 80°C for 2 hours, H-type molecular sieves were obtained. The product sample was recorded as S-4.

[0044] The XRD spectrum of sample S-4 is Figure 1 The XRD pattern of sample S-1 is shown in Fig. 1, which has the same characteristics as SSZ-13 and SSZ-23 eutectic molecular sieve.

[0045] The molar ratio of silicon oxide to aluminum oxide in the above-mentioned molecular sieve is 13, and the rare earth content in the above-mentioned molecular sieve is 1.6% based on the dry weight of the molecular sieve.

[0046] The sample S-4 was subjected to pure hydrocarbon micro-reaction evaluation after hydrothermal aging at 800°C under 100% steam for 17h, and the conversion rate, product yield and other data of the micro-reaction evaluation are shown in Table 1.

[0047] Example 5

[0048] This example illustrates the rare earth-containing eutectic molecular sieve and the preparation thereof.

[0049] To 64.64g of deionized water, 2.39g of disodium ethylenediaminetetraacetate and 2.62g of anhydrous lanthanum chloride were added and stirred for 30min, and then 2.09g of sodium hydroxide, 49.00g of N,N,N-trimethyl-1-adamantylammonium hydroxide solution (25% by mass fraction) and 1.34g of SB powder (containing Al2O3 at a mass fraction of 73.6%) were sequentially added to the solution, and the solution was stirred for 15min, and then 20g of white carbon black (containing SiO2 at a mass fraction of 73.2%) was added to the solution, and the solution was stirred for dispersion at room temperature for 3h, and then the solution was transferred to a hydrothermal kettle, and crystallization was carried out at 170°C for 60h, and then the product was filtered, washed until the pH was 7-8, and dried at 120°C for 12h, and then calcined at 600°C for 6h to obtain a rare earth lanthanum-containing SSZ-13 and SSZ-23 eutectic molecular sieve, and then the molecular sieve was exchanged with a soluble ammonium salt at 80°C for 2h to obtain a hydrogen type molecular sieve, and the product sample was recorded as S-5.

[0050] The XRD pattern of sample S-5 is shown in Fig. 1, which has the same characteristics as SSZ-13 and SSZ-23 eutectic molecular sieve. Figure 1 The XRD pattern of sample S-1 is shown in Fig. 1, which has the same characteristics as SSZ-13 and SSZ-23 eutectic molecular sieve.

[0051] The molar ratio of silicon oxide to aluminum oxide in the above-mentioned molecular sieve is 26, and the rare earth content in the above-mentioned molecular sieve is 7.4% based on the dry weight of the molecular sieve.

[0052] The sample S-4 was subjected to pure hydrocarbon micro-reaction evaluation after hydrothermal aging at 800°C under 100% steam for 17h, and the conversion rate, product yield and other data of the micro-reaction evaluation are shown in Table 1.

[0053] Comparative Example 1

[0054] This comparative example illustrates the preparation of SSZ-23 molecular sieve and the physical and chemical properties thereof.

[0055] To 30.42 g of deionized water, 1.39 g of sodium hydroxide, 37.83 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 19.49%) and 0.59 g of sodium aluminate were added and stirred for 30 minutes. Then, 20 g of solid silica gel (containing 77.4% SiO2 mass fraction) was added and dispersed with stirring at room temperature for 3 hours. The sol was transferred to a hydrothermal autoclave and crystallized at 160°C for 60 hours. The sol was filtered and washed to pH = 7-8, dried at 120°C for 12 hours, and then calcined at 600°C for 3 hours. After that, the SSZ-23 molecular sieve was obtained, and the sample was recorded as D-1.

[0056] The XRD spectrum of sample D-1 is as follows Figure 1 As shown in D-1, Figure 1 It can be seen that characteristic peaks of SSZ-23 molecular sieve appear at 8.1°, 8.5°, 9.5°, 10.5°, and 18.5°.

[0057] Comparative Example 2

[0058] This comparative example illustrates the preparation of SSZ-13 molecular sieve and its physical and chemical properties.

[0059] To 39.9 g of deionized water, 1.32 g of sodium hydroxide, 25.22 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 19.49%) and 1.48 g of sodium aluminate were added and stirred for 30 minutes. Then, 20 g of solid silica gel (containing 77.4% SiO2 mass fraction) was added and dispersed with stirring at room temperature for 3 hours. The sol was transferred to a hydrothermal autoclave and crystallized at 160°C for 60 hours. The sol was filtered and washed to pH = 7-8, dried at 120°C for 12 hours, and then calcined at 600°C for 6 hours. After that, the SSZ-13 molecular sieve was obtained after exchange with a soluble ammonium salt at 80°C for 2 hours. The sample was recorded as D-2.

[0060] The XRD spectrum of sample D-2 is as follows Figure 1 As shown in D-2, Figure 1 It can be seen that characteristic peaks of SSZ-13 molecular sieve appear at 9.5°, 13.0°, 16.1°, 17.9°, and 20.8°.

[0061] It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that, without adding a complexing agent and a rare earth compound and under the same molecular sieve crystallization conditions (crystallization at 160°C for 60 hours), SSZ-23 molecular sieve and SSZ-13 molecular sieve are obtained respectively due to the different silicon-to-aluminum ratio ranges synthesized by the two molecular sieves. After adding a complexing agent and a rare earth compound, a molecular sieve that is a eutectic of SSZ-13 and SSZ-23 and contains rare earth oxides can be obtained.

[0062] The following comparative examples 3, 4, and 5 illustrate the conventional SSZ-13 molecular sieve synthesis, rare earth modification process, and catalytic reaction performance, and are compared with the above-mentioned examples 1, 2, and 3 having the same silicon-aluminum ratio and rare earth content.

[0063] Comparative Example 3

[0064] This comparative example illustrates the preparation, rare earth modification and physicochemical properties of SSZ-13 molecular sieve.

[0065] 1.32 g of sodium hydroxide, 25.22 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 19.49%) and 1.48 g of sodium aluminate were added to 39.9 g of deionized water and stirred for 30 minutes. Then, 20 g of solid silica gel (containing 77.4% by mass of SiO2) was added and dispersed at room temperature with stirring for 3 hours. The sol was transferred to a hydrothermal autoclave and crystallized at 160°C for 60 hours. It was filtered and washed to a pH of 7-8, dried at 120°C for 12 hours, and then calcined at 600°C for 6 hours. After that, it was exchanged with a soluble ammonium salt at 80°C for 2 hours to obtain SSZ-13 molecular sieve. 10 g of the above molecular sieve (dry basis 92%) was added to a solution prepared by 0.42 g of LaCl3 and 13 g of deionized water, uniformly mixed, impregnated, dried, and calcined at 550°C in an air atmosphere for 2 hours to obtain a sample designated D-3.

[0066] The molar ratio of silicon oxide to aluminum oxide is 28, based on the dry weight of the molecular sieve, and the rare earth content in the molecular sieve is 2.8%.

[0067] After hydrothermal aging of the D-3 sample at 800°C and 100% steam for 17 h, a pure hydrocarbon micro-reaction evaluation was performed. The micro-reaction evaluation conversion rate, product yield and other data are listed in Table 1.

[0068] Comparative Example 4

[0069] This comparative example illustrates the preparation, rare earth modification and physicochemical properties of SSZ-13 molecular sieve.

[0070] 0.62 g of sodium hydroxide, 50.26 g of N, N, N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction of 19.49%) and 2.11 g of sodium aluminate were added to 47.85 g of deionized water and stirred for 30 min, then 20 g of solid silica gel (containing 77.4% by mass of SiO2) was added, and the mixture was stirred and dispersed at room temperature for 3 h. The sol was transferred to a hydrothermal autoclave and crystallized at 160 ° C for 60 h, filtered, washed to pH = 7-8, dried at 120 ° C for 12 h, then calcined at 600 ° C for 6 h, and then exchanged with a soluble ammonium salt at 80 ° C for 2 h to obtain SSZ-13 molecular sieve; 15 g of the above molecular sieve (dry basis 92%) was added with 2.73 g of A solution prepared by mixing Y(NO3)3·6H2O and 20g of deionized water was uniformly mixed, impregnated, dried, and calcined at 550℃ in air atmosphere for 2h to obtain a sample named D-4.

[0071] The molar ratio of silicon oxide to aluminum oxide is 19, based on the dry weight of the molecular sieve, and the rare earth content in the molecular sieve is 5.3%.

[0072] After hydrothermal aging of the D-4 sample at 800°C and 100% steam for 17 h, a pure hydrocarbon micro-reaction evaluation was performed. The micro-reaction evaluation conversion rate, product yield and other data are listed in Table 1.

[0073] Comparative Example 5

[0074] This comparative example illustrates the preparation, rare earth modification and physicochemical properties of SSZ-13 molecular sieve.

[0075] 1.27 g of sodium hydroxide, 33.51 g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide solution (mass fraction 19.49%) and 1.62 g of sodium aluminate were added to 38.13 g of deionized water and stirred for 30 min. Then, 20 g of solid silica gel (containing 77.4% by mass of SiO2) was added and dispersed at room temperature with stirring for 3 h. The sol was transferred to a hydrothermal autoclave and crystallized at 160°C for 60 h. It was filtered and washed to a pH of 7-8, dried at 120°C for 12 h, and then calcined at 600°C for 6 h. After exchange with a soluble ammonium salt at 80°C for 2 h, SSZ-13 molecular sieve was obtained. 15 g of the above molecular sieve (dry basis 92%) was added to a solution prepared by 1.24 g of CeCl3·7H2O and 20 g of deionized water, the mixture was uniformly mixed, impregnated, dried, and calcined at 550°C in air for 2 h to obtain sample D-5.

[0076] The molar ratio of silicon oxide to aluminum oxide is 25, and the rare earth content of the molecular sieve is 3.9% based on the dry weight of the molecular sieve.

[0077] The D-5 sample was hydrothermally aged at 800℃ under 100% steam for 17h, and then subjected to pure hydrocarbon micro-reaction evaluation. The conversion rate, product yield and other data of the micro-reaction evaluation are shown in Table 1.

[0078] Comparative Example 6

[0079] This comparative example illustrates the preparation, rare earth modification and physicochemical properties of SSZ-23 molecular sieve.

[0080] This comparative example is compared with Example 4 which has the same silicon-aluminum ratio and rare earth content.

[0081] To 40.5g of water, 2.36g of sodium hydroxide, 5.12g of quinuclidin-3-ol (mass fraction of 98%) and 3.87g of SB powder (containing Al2O3 mass fraction of 73.6%) were added and stirred for 30min, then 30g of solid silica gel (containing SiO2 mass fraction of 77.4%) was added and stirred for dispersion at room temperature for 3h. The sol was transferred to a hydrothermal kettle and crystallized at 145℃ for 96h. After filtration and washing to pH=7-8, it was dried at 120℃ for 12h, and then calcined at 600℃ for 6h. After being exchanged with a soluble ammonium salt at 80℃ for 2h, SSZ-23 molecular sieve was obtained. 20g (dry basis 90%) of the above-mentioned molecular sieve was added to a solution of 0.52g LaCl3 and 28g of deionized water, and uniformly mixed, impregnated, dried and calcined at 550℃ in air for 2h to obtain a sample, which is denoted as D-6.

[0082] The molar ratio of silicon oxide to aluminum oxide was 13, and the rare earth content in the above-mentioned molecular sieve was 1.6% based on the dry weight of the molecular sieve.

[0083] The D-6 sample was hydrothermally aged at 800℃ under 100% steam for 17h, and then subjected to pure hydrocarbon micro-reaction evaluation. The conversion rate, product yield and other data of the micro-reaction evaluation are shown in Table 1.

[0084] Table 1

[0085] Sample number S-1 S-2 S-3 S-4 S-5 D-3 D-4 D-5 D-6 n(Si02) / n(Al203) 28 19 25 13 26 28 19 25 13 Rare earth oxide content / wt% 2.8 5.3 3.9 1.6 7.4 2.8 5.3 3.9 1.6 Micro-reaction conversion rate / % 92 88 89 93 85 72 77 75 71 Ethylene yield / wt% 2.4 2.7 2.5 2.8 2.2 0.7 0.9 0.9 1.1 Propylene yield / wt% 19.6 18.7 18.9 19.2 18 17.3 18.3 17.6 17.1 Butene yield / wt% 27.3 28.8 28.2 29.4 26.3 25.5 25.9 25.1 24.4

[0086] As can be seen from the data in Table 1, the rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieves prepared by the present application exhibit excellent reaction conversion rate and high ethylene, propylene and butylene yield, especially ethylene yield, in the reaction of catalytic cracking of 1-octene. The reaction conversion rate and ethylene, propylene and butylene yield of the rare earth type SSZ-13 molecular sieve or the rare earth type SSZ-23 molecular sieve obtained by the traditional impregnation method are lower than those of the rare earth-containing SSZ-13 and SSZ-23 eutectic molecular sieves prepared in situ by the present application.

Claims

1. A method for preparing a rare earth-containing eutectic molecular sieve, characterized in that The invention comprises the following steps: uniformly mixing a complexing agent, water and a soluble rare earth compound to obtain a mixture A; adding an alkali source, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, an aluminum source and a silicon source to the mixture A, and uniformly mixing to obtain a mixture B; performing a crystallization reaction on the mixture B under hydrothermal conditions and recovering the crystallized product to obtain a eutectic molecular sieve containing rare earths SSZ-13 and SSZ-23; in the mixture A, the molar ratio of the complexing agent and the soluble rare earth compound is 0.05; and the molar ratio of the complexing agent and the soluble rare earth compound is 0.

05. The ratio is 0.1 to 3:1, and the soluble rare earth compound is calculated as rare earth oxide; in the mixture B, the molar ratio of water, N,N,N-trimethyl-1-adamantyl ammonium hydroxide, aluminum source and silicon source is 50 to 1000:0.4 to 10:1:5 to 50, the aluminum source is calculated as Al2O3, and the silicon source is calculated as SiO2; the molar ratio of the soluble rare earth compound to the silicon source is 1:10 to 1000, the soluble rare earth compound is calculated as rare earth oxide, and the silicon source is calculated as SiO2.

2. The preparation method according to claim 1, wherein The complexing agent is selected from at least one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, triethanolamine, and triethylamine.

3. The preparation method according to claim 1, wherein The soluble rare earth compound is selected from at least one of lanthanum chloride, yttrium nitrate and cerium nitrate.

4. The preparation method according to claim 1, wherein The alkali source is selected from sodium hydroxide and / or potassium hydroxide.

5. The preparation method according to claim 1, wherein The N,N,N-trimethyl-1-adamantyl ammonium hydroxide is in the form of an aqueous solution with a mass fraction of 15 to 30%.

6. The preparation method according to claim 1, wherein The aluminum source is selected from at least one of SB powder, aluminum alcoholate, aluminum oxide, aluminum hydroxide, aluminum sulfate and gibbsite; the silicon source is selected from at least one of silica sol, silicon dioxide, white carbon black, silicate and solid silica gel.

7. The preparation method according to claim 1, wherein The crystallization reaction is carried out under a closed condition at a temperature of 140° C. to 200° C. for 18 hours to 168 hours.

8. The rare earth-containing eutectic molecular sieve obtained by the preparation method according to any one of claims 1 to 7.

9. The rare earth-containing eutectic molecular sieve according to claim 8, characterized in that In the XRD diffraction spectrum of the eutectic molecular sieve, characteristic peaks of SSZ-13 molecular sieve appear at 9.5°, 13.0°, 16.1°, 17.9°, and 20.8°, and characteristic peaks of SSZ-23 molecular sieve appear at 8.1°, 8.5°, 9.5°, 10.5°, and 18.5°. The molar ratio of silicon oxide to aluminum oxide is 5 to 50, and the rare earth content is 0.5 to 10% calculated as rare earth oxide and based on the dry weight of the eutectic molecular sieve.

10. The rare earth-containing eutectic molecular sieve according to claim 8, wherein The molar ratio of silicon oxide to aluminum oxide is 15 to 35.

11. The rare earth-containing eutectic molecular sieve according to claim 8, wherein: The rare earth content is 1-6%.

12. The rare earth-containing eutectic molecular sieve according to claim 8, wherein The rare earth is selected from at least one of lanthanum, cerium and yttrium.

13. Use of the rare earth-containing eutectic molecular sieve according to claim 8.

14. Use according to claim 13, characterized in that The rare earth-containing eutectic molecular sieve is used in catalytic cracking and catalytic cracking as an active component of a catalyst or an auxiliary agent.

Citation Information

Patent Citations

  • Rare earth Y-type molecular sieve and preparation method thereof

    CN103508467A

  • Zeolite SSZ-13 and its method of preparation

    US4544538A

  • Zeolite SSZ-23

    US4859442A

  • Catalyst for preparing olefin by conversion of methanol as well as preparation and application thereof

    CN102451749A

  • An alumina silicate zeolite-type material for use as a catalyst in selective catalytic reduction and process of making thereof

    CN104797337A